Tools based on proprietary and free/open source geospatial software for CO emission maps analysis and comparison - Migliaccio, Federica; Carrion, Daniela; Zambrano, Cynthia (Applied geomatics, 2012)
The increasing availability of data monitoring the phenomena that occur on the Earth makes it necessary to provide ad hoc tools allowing the researchers to exploit efficiently all information. The study presented in this paper has been dedicated to the design and implementation in a GIS environment of tools and indices for the analysis and inter-comparison of several datasets representing CO emissions at a global level. The objective of the work was to provide the scientists with an instrument for the consultation and processing of CO emission datasets, with as much automation as possible, besides guided setting of the parameters and interface for graph generation. Both proprietary and open source software have been considered, highlighting their advantages and disadvantages. The use of proprietary software (ArcGIS 9.3) was requested by the users; for a more efficient customisation the implementation involved also the use of Python 2.5 language and of the Matplotlib library. Then the same kind of tools were implemented in a new module of the GRASS software (version 6.4), developed in C language. In this paper the tools are presented together with examples of CO emission datasets inter-comparisons.